Linking Self-Leadership, Adversity Quotient, and Organizational Commitment : The Moderating Role of Emotional Intelligence - Ritonga, Lastry Khoriza; Pareke, Fahrudin JS (Jambura Economic Education Journal, 2025)
Teachers play a role in shaping the quality of human resources. Teachers' organizational commitment is a key factor in creating an effective and sustainable learning environment. This study aims to examine the influence of self-leadership and adversity quotient on teachers' organizational commitment, as well as to analyze the role of emotional intelligence as a moderating variable. This study employs a quantitative approach using proportionate stratified sampling, involving 276 teachers from elementary, junior high, and senior high schools in Seluma District. Data were collected via an online questionnaire, followed by validity and reliability tests, and then analyzed using multiple linear regression and moderation tests using the PROCESS macro. The results indicate that self-leadership and adversity quotient have a positive and significant effect on teachers' organizational commitment. Additionally, emotional intelligence was found to moderate the relationship between self-leadership and adversity quotient on organizational commitment. These findings emphasize the importance of developing self-leadership, adversity quotient, and emotional intelligence in enhancing teachers' organizational commitment. The practical implications of this study are the need for self-development and emotional intelligence training for teachers, as well as institutional support to create a conducive and sustainable work environment